PENGARUH FILSAFAT POSITIVISME DALAM PENEGAKAN HUKUM DI INDONESIA - -, Maryanto - (Wacana Hukum, 2012)
Abstract: The principles of legal certainty very dominating in the law enforcement inIndonesia. The principle of legal certainty that comes from century XVII/XVIIIin Europe is a great idea from tangible in writing, made by competentauthorities. The term of analytical jurisprudence indicates that the law shoulbe removed from the study of metaphysics. Doctrine analytical jurisprudenceannnot be implemented just after about two centuries introduction by theoriginators. It is doe to changes and development of society so rapidly. Forthose in law enforcement must look spirit and the time made law. Don’t justlook at the text but the context of the law with the purpose of the law.Key word: law enforcement, Analytical Jurisprudence,religion models of reinforcement.